A brief history of feminism - Schrupp, Antje, 1964- (MIT Press, 2017)
An engaging illustrated history of feminism from antiquity through third-wave feminism, featuring Sappho, Mary Magdalene, Mary Wollstonecraft, Sojourner Truth, Simone de Beauvoir, and many others.